Penerapan Model Pembelajaran Learning Cycle 5E untuk Meningkatkan Partisipasi Aktif Siswa Kelas X-3 SMA Negeri Gondangrejo Karanganyar Tahun Pelajaran 2015/2016 - Nurhuda, Haris; Probosari, Riezky Maya; Prayitno, Baskoro Adi (Universitas Sebelas Maret, 2016)
The aim of this research is to improve students active participation through the aplication of the learning cycle 5E model in class X-3 SMAN Gondangrejo in academic year 2015/2016. This research was a classroom action research with two cycles conducted from March until April 2016. Each cycle consisted of 4 phases, i.e. planning, acting, observing, and reflecting. The participants of the research are 37 students of grade X-3 SMAN Gondangrejo Karanganyar. Data was obtained from observation, documentation, and interview. The main data of active participation includes several aspects as follows: question, opinions, and discussion. Data was analyzed descriptively, and validated using a triangulation method. The research procedure used was the spiral method by Kemmis and Mc.Taggart. The result of the research shows that learning cycle 5E increased the students’ active participation.. Observations show that the number of students who asked questions on pre-action of three students, or 8%, the first cycle of 10 students or 27%, and the second cycle 20 students or 54%. Students who express opinions on the pre-action as much as four students, or 10%, the first cycle of 15 students or 40%, and the second cycle 19 students or 51%. The average score of student participation in discussions on pre-action was 2,17 points, the first cycle of 2,79 points and the second cycle of 3,65 points.Key Words : learning cycle 5E, active participation, questions, opinions, discussion